How can the African Continental Free Trade Area help Green African Trade? - (:unkn) unknown (My University, 2025)
Africa has contributed little to Climate Change (CC), though being hardest hit, especially African agriculture, both in the short-run (fast-onset events like droughts and floods) and in the long-run through lower productivity in agriculture (slow-onset events from warming). The paper starts with a template of the dimensions of the trade environment nexus in Africa, then reviews evidence on the role of international trade in helping African countries mitigate and adapt to CC. Much of the focus is on the AfCFTA and on the contribution of the AERC GVC phase II to the state of knowledge. [...]
Keywords: African Research